KINERJA PEMBUNGAAN DAN PRODUKSI TANAMAN JAGUNG UMUR MASAK SUSU DI LAHAN PASIR PADA PENGGUNAAN BIO MULSA - B. Suwignyo; B.W. Pratomo; N. Umami; B. Suhartanto (Universitas Tribhuwana Tunggadewi, 2015)
The study aimed to determine fowering and production performance of milk stage corn planted in critical sandy land with bio mulch. Plastic mulch and bio mulch (feedstuff used), were used on 3 (three) beds planted with Pioneer® seed corn. Seeds were planted with 25 x 50 cm in sandy land Jangkaran Village, Temon, Kulon Progo, Yogyakarta. Litter manure waste was used as basal fertilizer by spreaded over the beds at the level 7.5 t/ha. Corn seed planted on the bed without basal fertilizer and mulch as a control. Chemical fertilizers, urea and SP-36 are given in equal amounts and the corresponding frequency written on the label. Water was given to corn plant every other day. Quantity of flower was observed since the first time produce flower up to harvested at 10 weeks, while production was determined from total weight of whole plant harvested. The study is based on completely randomized design (CRD) and the data were analyzed by ANOVA with SPSS advanced analysis of LSD. Corn plant with bio mulch produced significantly higher of flower and whole plant compare with control but not significantly higher compare with plastic mulch. However, bio mulch always has highest level of flower 34.4% compare with plastic mulch 17.7% and control 9.2; highest production level of fresh whole plant13.3, plastic mulch 12.93 and 3.91 t/ha. Utilization of mulch has significant effect on the quantity of flower and production level